2012
DOI: 10.1007/s00396-012-2675-1
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of topological entanglements during the contact of glassy polymers

Abstract: Fracture energy (G) of the symmetric amorphous polystyrene (PS)-PS interfaces that were partially healed at temperatures (T) below the glass transition temperature of the bulk ( T bulk g ) has been measured at ambient temperature and compared with those reported in the literature (G 0 ) for the symmetric PS-PS interfaces that were fully healed at T>T bulk g . It has been shown that G developed at T Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Therefore, the reported G c values can be attributed to irreversible processes such as chain pullouts, scissions, or disentanglement processes during debonding, which would only be possible if the polymer films bonded as a result of chain interpenetration across the interface during the prior deformation. Quantitative levels of fracture toughnesses reported in this study are comparable to those obtained in the literature, 34 where debonding, after bonding through interdiffusion, is attributed to irreversible chain pullouts, scissions, or disentanglement processes. Other bonding mechanisms such as acid–base interactions, electrostatic/capillary effects, and mechanical interlocking of asperities cannot be considered responsible for the bonding behavior reported in this study; this is because, at large bulk plastic deformation levels, the interfacial contact area between the films increases rapidly, and if any of these factors were predominant then they would lead to a monotonic increase in bonding with the imposed plastic strain across all films.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the reported G c values can be attributed to irreversible processes such as chain pullouts, scissions, or disentanglement processes during debonding, which would only be possible if the polymer films bonded as a result of chain interpenetration across the interface during the prior deformation. Quantitative levels of fracture toughnesses reported in this study are comparable to those obtained in the literature, 34 where debonding, after bonding through interdiffusion, is attributed to irreversible chain pullouts, scissions, or disentanglement processes. Other bonding mechanisms such as acid–base interactions, electrostatic/capillary effects, and mechanical interlocking of asperities cannot be considered responsible for the bonding behavior reported in this study; this is because, at large bulk plastic deformation levels, the interfacial contact area between the films increases rapidly, and if any of these factors were predominant then they would lead to a monotonic increase in bonding with the imposed plastic strain across all films.…”
Section: Resultssupporting
confidence: 86%
“…There have been various reports of polymer adhesion below the glass transition temperature 35–38 through the application of a mild contact pressure over experimental timescales of minutes and hours. In these studies, sub‐T g bonding was attributed to a rubbery‐like surface layer present on the free surface of the polymers, where the glass transition temperature is naturally reduced, and the molecular mobility is enhanced 39–42 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the quantitative levels of interface toughness G c obtained here, with a maximum value nearly 10 J/m 2 , can be attributed to the irreversible processes of chain pull-outs, disentanglement and/or scissions during debonding, which could only happen if plasticity-induced molecular mobilization and chain-interpenetration had led to bonding. It is worth emphasizing that studies on polymer adhesion leading to G c values up to 1.2 J/m 2 and 2.0 J/m 2 , respectively 31 49 , have attributed such levels of fracture toughnesses due to chain interdiffusion and irreversible chain pull-out mechanisms during debonding. The levels of fracture toughnesses reported in our study are comparably larger than those reported in these studies, and therefore affirm that in our case bonding occured via chain interpenetration and debonding involves irreversible chain pull-out processes.…”
Section: Resultsmentioning
confidence: 99%
“…In the past two decades, there have been reports of evolving polymer adhesion due to interdiffusion at temperatures somewhat below the bulk T g , with relatively long healing times of order several minutes 27 28 , hours 29 30 , and even up to a day 31 . Interpretations of such studies have suggested that bonding of a glassy polymer via molecular interdiffusion, even at temperatures below the bulk T g , is possible over such time scales if a near-surface layer of the polymer remains in a rubbery state.…”
mentioning
confidence: 99%
“…The entanglement density can be directly related to the viscoelastic response of high molecular weight polymer melts. 3,10,11 Experiments have suggested that entanglements strongly affect the mechanical properties of interfaces between glassy polymers, 5,[12][13][14][15][16][17] and many theoretical models also assume that entanglements play a critical role. 5,[18][19][20] In this Letter, we present results from large-scale molecular dynamics (MD) simulations of the interdiffusion between highly entangled immiscible polymers.…”
mentioning
confidence: 99%